Political Communication in Africa
XV, 246 p.
Keywords: This book offers a comprehensive account of the nature and development of political communication in Africa. In light of the growing number of African states now turning towards democratic rule, as well as the growing utilization of information technologies in Africa, the contributors examine topics such as: the role of social media in politics, strategic political communication, political philosophy and political communication, Habermas in Africa, gender and political communication, image dilemma in Africa, and issues in political communication research in Africa, and identify the frontiers for future research on political communication in Africa. .